Dapagliflozin combined with methylcobalamin in the treatment of type 2 diabetes mellitus with peripheral neuropathy: a systematic review and meta-analysis - Deng, Xiao-Long; Wu, Ren; Lin, Xuan-Xia; Liang, Jia-Jian; Huang, Han-Wei (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a prevalent chronic metabolic disorder, with diabetic peripheral neuropathy (DPN) being one of its most common complications. Current treatments primarily aim at glycemic control and symptom relief, yet long-term efficacy is often insufficient. Dapagliflozin, an SGLT-2 inhibitor, and methylcobalamin, the active form of vitamin B12, have demonstrated potential in managing DPN. This systematic review assesses the efficacy and safety of their combined use.MethodsThis study synthesized randomized controlled trials (RCTs) from major databases up to the September 30, 2024, focusing on dapagliflozin combined with methylcobalamin for treating DPN in T2DM patients. Statistical analysis was performed using RevMan 5.4. The risk of bias was assessed with the Cochrane Risk of Bias 2.0 (ROB 2.0) tool. Outcomes included the overall effective rate (OER), common peroneal motor nerve conduction velocity (CPMNCV), common peroneal sensory nerve conduction velocity (CPSNCV), median motor nerve conduction velocity (MMNCV), and median sensory nerve conduction velocity (MSNCV), fasting plasma glucose (FPG), 2-hour postprandial blood glucose (2hPG), glycosylated hemoglobin (HbA1c), and rate of adverse events (RAE).ResultsSeven RCTs met inclusion criteria. The combination therapy significantly improved OER (odds ratio (OR): 5.05; 95% confidence interval (CI): 2.60–9.81), CPMNCV (MD: 3.93 m/s; 95% CI: 2.16–5.70; P<0.01), CPSNCV (MD: 3.36 m/s; 95% CI: 2.74–3.98; P<0.01), MMNCV (MD: 4.71 m/s; 95% CI: 3.90–5.52; P<0.01), and MSNCV (MD: 3.05 m/s; 95% CI: 2.19–3.90; P<0.01). Glycemic control also improved, with reductions in FPG (MD, 95% CI: -1.19 mmol/L [-1.40, -0.98]; P<0.01), 2hPG (MD, 95% CI: -1.36 mmol/L[-1.44, -1.27]; P<0.01), and HbA1c levels (MD, 95% CI: -0.87% [-1.04, -0.71]; P<0.01). There was no significant increase in adverse events (OR: 0.37; 95% CI: 0.07–2.03; P=0.25).ConclusionDapagliflozin combined with methylcobalamin appears to be an effective and safe therapeutic strategy for managing DPN in T2DM patients, improving both nerve function and glycemic control.